Comparison of the effectiveness of Aloe Vera gel with 2% Nitrofurazone ointment on the healing of superficial partial-thickness burns: A randomized clinical trial study - Parichehr Sabaghzadeh Irani; Hadi Ranjbar; Shokoh Varaei; Sanaz Bostani; Omalbanin Akbari; Maryam Askarymahani (Tehran University of Medical Sciences, 2021)
Background & Aim: Routine treatment of burn injuries is dressing with Nitrofurazone ointment. It has several complications including sensitivity. Aloe vera is a traditional treatment for wound healing.  This study aimed to compare the effectiveness of Aloe Vera gel with Nitrofurazone ointment in the healing of superficial partial-thickness burns. Methods & Materials: The present study was a split body controlled clinical trial which was carried out on 30 patients with superficial partial-thickness burns. The study was conducted in the Shafa Hospital in Kerman, Iran in 2016. The sample was recruited from patients who had at least two burns, each burn on an alternate side of the body. Samples were allocated to two groups that received Aloe Vera gel or 2% Nitrofurazone ointment on their burns. Bates-Jensen Wound assessment tool was used to evaluate the healing of burns. Statistical analysis was conducted by SPSS-16 and using the repeated measure ANOVA. Results: The repeated measure ANOVA showed that there was a significant change in the score of BWAT in all areas during the intervention period ( p=0.001), but The trend of healing in the two groups during the intervention period was not significantly different( p=0.098). Conclusion: Based on this study it looks like Aloe vera gel is as effective as  2% Nitrofurazon ointment in healing wounds.